Xist drives spatial compartmentalization of DNA and protein to orchestrate initiation and maintenance of X inactivation. (June 2020) - Strehle, Mackenzie; Guttman, Mitchell
Abstract: X chromosome inactivation (XCI) is the process whereby one of the X chromosomes in female mammalian cells is silenced to equalize X-linked gene expression with males. XCI depends on the long noncoding RNA Xist, which coats the inactive X chromosome in cis and triggers a cascade of events that ultimately lead to chromosome-wide transcriptional silencing that is stable for the lifetime of an organism. In recent years, the discovery of proteins that interact with Xist have led to new insights into how the initiation of XCI occurs. Nevertheless, there are still various unknowns about the mechanisms by which Xist orchestrates and maintains stable X-linked silencing. Here, we review recent work elucidating the role of Xist and its protein partners in mediating chromosome-wide transcriptional repression, as well as discuss a model by which Xist may compartmentalize proteins across the inactive X chromosome to enable both the initiation and maintenance of XCI.